Actual Problems of the Development and Investment Environment of the Agrarin Cooperation (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In this article there are considered the basic problems of economic efficiency in the agrarian producersʼ activity. There are also determined the main goals and tasks of the agricultural industrial cooperative a well as its classification features. There were established the basic factors and prerequisites for effective producersʼ activity, which are lying in using the cooperative form of conducting the agriculture. The dynamics of the development of agrarian service cooperatives is investigated for the period of last six years of Ukraineʼs regions and also according to the directions of their activity. It is found out the number of agrarian attendant cooperatives, which really perform agrarian activity and pay taxes, give services and sell such kinds of product as: dairy, grain, fruit and vegetables. There are determined the basic classificational features of investment resources of agricultural cooperatives. And there is also built the scheme of their classificational kinds.
Keywords: agricultural cooperatives, economic efficiency, investmentsupport